On the 2-dimensional N=2 Wess-Zumino model on the lattice; From Dirac-Kähler formalism to the Nicolai mapping - Aratyn, H.; Bessa, P. F.; Zimerman, A. H. (Springer Nature, 1985)
We present a treatment of the supersymmetric Wess-Zumino N=2 two dimensional model in the discrete space-time. We propose a pure differential form approach to the superspace formalism which enables us to obtain the corresponding supersymmetric Dirac-Kähler Lagrangean. We show that our discretized supersymmetric model can be alternatively constructed from Nicolai mapping on the lattice. © 1985 Springer-Verlag.